OUTCOMES OF ARTHROSCOPIC BANKART REPAIR IN THE PEDIATRIC AND ADOLESCENT POPULATION: HIGH RATES OF FAILURE. Issue 3 (31st March 2019) - Pandya, Nirav K.; Kramer, Jonathan
BACKGROUND: Shoulder instability is an increasingly common problem in the pediatric and adolescent population. As with anterior cruciate ligament reconstruction, surgical intervention in this population is becomingly increasingly common. Yet, although failure rates are much higher in this active population there has been limited examination of this population in the literature. The purpose this study was to review treatment of adolescent shoulder instability and to discuss factors influencing its management; particularly recurrent instability. METHODS: A retrospective cohort study was performed at a single center. Inclusion criteria consisted of all adolescent aged patients identified who (1) had complaints of shoulder instability, (2) had radiographic findings consistent with anterior-inferior capsulolabral injury, (3) had documented evidence of a dislocation event, and (4) underwent arthroscopic shoulder stabilization. Patient demographics, pre-operative history and physical, imaging, surgical details, and post-operative complications were analyzed. RESULTS: Thirty-six patients were identified with a mean follow-up 3.07 ± 1.2 years. The average patient age at the time the index procedure was 16.03 ± 1.67 years. All patients underwent arthroscopic shoulder stabilization consisting of arthroscopic Bankart repair. Five patients also underwent a remplissage. Nine patients (25.0%) developed a repeat dislocation following surgery. This occurred on average 20.67 months postoperatively (range 5-51 months). No single sport was associated with a statistically significant increased risk of re-dislocation. American football was the most common sport in both the stable and re-dislocated groups. Patients who re-dislocated had a higher frequency of a Hill-Sachs lesion on MRI (89%) compared to those who did not re-dislocate (52%) (p=0.048). Off-track lesions were not associated with repeat instability. CONCLUSIONS / SIGNIFICANCE: The current study demonstrates that adolescent patients treated with arthroscopic shoulder stabilization have a high rate of recurrence of shoulder dislocations, particularly in the setting of a concomitant Hills-Sachs lesion. Patients may benefit from more aggressive stabilization strategies and techniques. Further prospective multi-center studies are necessary to determine the reasons for the high rate of re-dislocation in this population and develop strategies for prevention.